Dalang And Sinden As A Form Of “Loro-Loro ning Tunggal” In Wayang Golek Purwa Performances - Maulana, Marsel Ridky; Prayuga Sutisna, Diynan; Arya Saputra, Raffa (JPKS (Jurnal Pendidikan dan Kajian Seni), 2025)
Wayang Golek Purwa is a performing art that uses wooden puppets as the main media. This performance combines various elements, such as play and arrangement, which include language, sound, form, and movement. The relationship between the two not only represents a unity, but also reflects the philosophy of “Loro-Loro Ning Tunggal”, which describes two entities that are united. This research aims to analyze the relationship between the puppeteer and sinden and explore the application of this philosophy in Wayang Golek performance art. The method used in this research is a literature study, namely by tracing classical literature sources that discuss the role of puppeteers and sinden as a unit in Purwa Wayang Golek performances. The results show that the philosophy of “Loro-Loro Ning Tunggal” is the basis for collaboration that produces harmony in artistic expression, both in the technical and aesthetic dimensions. The concept also reflects cultural values, such as cooperation, mutual respect, and balance, which are relevant not only in art, but also in the lives of its supporting communities. This study makes an important contribution in enriching the understanding of traditional art through cultural and philosophical perspectives.